Drilling and completion challenges and remedies of CO2 injected wells with emphasis to mitigate well integrity issues - Hossain, Mofazzal; Amro, M. (SPE, 2011)
CO2 emission is generally accepted to be one of the prime causes of global warming and climate change issues. In order to combat this global warming by reducing CO2 emissions, there are numerous pilot projects developed worldwide, where injection of CO2 for sequestration/storage, and Enhanced Oil/Gas Recovery (EOR/EGR) have been ongoing for many years. The well design and completion consideration of such CO2 injected wells, especially pertaining to well integrity, selection of downhole completion equipments, design of pressure containment for high pressure and highly corrosive environment, differs in many ways compared to typical injection wells in the oil field or natural gas storage projects. There are various well integrity failures, which are reported in the literature during drilling and completion of such wells either for EOR or CO2 sequestration projects. The monitoring of CO2 migration within the wells with time is also essential.In this study, the principle mechanisms involving well integrity issues including caprock and cementing integrity in CO2 injected wells are investigated at various operating conditions, based on comprehensive review of various field cases as published in the literature. The critical factors associated with well design failures, pressure containment, corrosion issues, tubing leakage, cementing problems, and selection of downhole equipments for well completion etc are identified. Based on the study, precise screening criteria are developed that enables the design and completion of CO2 injected wells for EOR and CO2 sequestration; thereby minimizing the chance of integrity failures. Results for different conditions will be presented and discussed to provide guide lines for mitigating the numbers of theses challenges with an emphasis to the successful design and completion of such wells. The key factors concerning monitoring of CO2 migration with time will be discussed.